2002
DOI: 10.1046/j.1439-0264.2002.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Musculus Extensor Digiti Medii Proprius and Musculus Extensor Digitorum Brevis Manus – A Case Report of a Rare Variation

Abstract: The musculus extensor digiti medii proprius and musculus extensor digitorum brevis manus are anomalous extensor muscles of the hand. During the routine dissection of a white male cadaver a musculus extensor digiti medii proprius was seen on both hands and a musculus extensor digitorum brevis manus was seen on the left hand. The extensor medii proprius has a belly originating from the distal third of the ulna near the extensor indicis proprius and its tendon is inserted into the dorsal aponeurosis of the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
12
1
Order By: Relevance
“…Some variant muscles on the dorsum of the forearm and hand, such as the extensor indicis proprius (EIP) (von Schroeder and Botte, 1995;Tan and Smith, 1998), extensor medii proprius (EMP) (von Schroeder and Bottle, 1991;Khaledpour and Schindelmeiser, 1993;Cigali et al, 2002), extensor digitorum brevis manus (EDBM) (Ogura et al, 1987;Khaledpour and Schindelmeiser, 1993;Cigali et al, 2002), and extensor pollicis et indicis accessorius (EPI) (Komiyama et al, 1999), have been described in detail by many authors. Nevertheless, the extensor indicis et medii communis (EIMC), which originates from the distal third of the ulna with two tendons insert into the index and long fingers, has not been reported in recent studies, except the articles of von Botte (1991, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some variant muscles on the dorsum of the forearm and hand, such as the extensor indicis proprius (EIP) (von Schroeder and Botte, 1995;Tan and Smith, 1998), extensor medii proprius (EMP) (von Schroeder and Bottle, 1991;Khaledpour and Schindelmeiser, 1993;Cigali et al, 2002), extensor digitorum brevis manus (EDBM) (Ogura et al, 1987;Khaledpour and Schindelmeiser, 1993;Cigali et al, 2002), and extensor pollicis et indicis accessorius (EPI) (Komiyama et al, 1999), have been described in detail by many authors. Nevertheless, the extensor indicis et medii communis (EIMC), which originates from the distal third of the ulna with two tendons insert into the index and long fingers, has not been reported in recent studies, except the articles of von Botte (1991, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have reported its prevalence ranging from 1% to 12% of cadavers. 2,[4][5][6][7][8]10 The current report shows the prevalence is at the middle of this range (7.4%). A higher incidence is reported by von Schroeder and Botte, 4 with a 12% prevalence of the EDM.…”
Section: Discussionmentioning
confidence: 54%
“…2,[4][5][6][7][8]10 According to Abu-Hijleh, "No clinical or surgical cases of such occurrence have been reported and therefore it is doubtful whether an accurate estimate of the prevalence of EDM can be made." 2 However, Pfeiffer 11 discovered an EDM while operating on the hand of a 28-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations